NURSE-PATIENT RELATIONSHIP IN THE PRE-SURGICAL PERIOD: A THEORETICAL REFLECTION IN THE LIGHT OF JOYCE TRAVELBEES THEORY - Berendina Elsina Bouwman Chistóforo; Ivete Palmira Sanson Zagonel; Denise S. Carvalho (Universidade Federal do Paraná, 2006)
This paper has the main objective of suggesting a theoretical reflection on the inter-relationship of the nursing team and patient in the pre-surgical period in order to strengthen the dimensions that take up the care actions in professional practice in the light of Joyce Travelbees Transpersonal Theory. Questioning emerges from the researchers daily work as a Nursing practitioner and Nursing teacher that experiences the work organization in this sector: a functional, technical and impersonal model, with daily preestablished routines. It emphasizes the importance of relationship to the patient through listening, perception, care, communication, considering the feelings facing a stressful situation such as, fear, doubt and emotional changes. It still points out the necessity of awareness in relation to care appraisal, the inter-relationship and still, the professional qualification in order to reach care humanization.